The Impact of Using Digital Children’s Literature Prathambooks.org on EFL College Students’ Vocabularies at UNP - Yuliani Yuliani; Leni Marlina (Journal of English Language Teaching, 2023)
Digital children’s literature website provides authentic and interesting reading media for EFL students. This research aims to investigate whether using digital children’s literature prathambooks.org has a good impact on EFL college students’ vocabularies. This study applied a quasi-experimental research design with a quantitative method. The sample was two classes consisting of 64 students in the English language education major who enrolled in Introduction to Literature subject for the 2022/2023 academic year. The data were gathered using pre-test and post-tests of EFL college students’ vocabularies consisting of 150 vocabularies taken from 15 selected stories on prathambooks.org. A collection of 15 stories completed with vocabulary exercises and vocabulary lists was used as the reading daily treatment within 15 days. The finding of this research shows an improvement in students’ familiarity with the vocabulary given. This research proves that employing digital children’s literature as reading media has a positive impact on EFL college students’ vocabularies.